Quality, reliability, security and robustness in heterogeneous networks : 7th International conference on heterogeneous networking for quality, reliability, security and robustness, QShine 2010, and dedicated short range communications workshop, DSRC 2010, Houston, TX, USA, November 17-19, 2010, Revised Selected Papers - Qiao, Daji; Zhang, Xi (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Conference on Heterogeneous Networking for Quality, Reliability, Security and Robustness, QShine 2010. The 37 revised full papers presented along with 7 papers from the allocated Dedicated Short Range Communications Workshop, DSRC 2010, were carefully selected from numerous submissions. Conference papers are organized into 9 technical sessions, covering the topics of cognitive radio networks, security, resource allocation, wireless protocols and algorithms, advanced networking systems, sensor networks, scheduling and optimization, routing protocols, multimedia and stream processing. Workshop papers are organized into two sessions: DSRC networks and DSRC security.